2015
DOI: 10.1179/1743676115y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride nanosheets reinforced glass matrix composites

Abstract: The effect of reinforcing boron nitride nanosheets (BNNSs) on the mechanical properties of an amorphous borosilicate glass (BS) matrix was studied. The BNNSs were prepared using liquid exfoliation method and characterised by transmission electron microscopy, scanning electron microscopy and X-ray diffraction (XRD) analysis. The average length was ,0.5 mm, and thickness of the nanosheets was between 4 and 30 layers. These BNNSs were used to prepare BS-BNNS composite with different loading concentrations of 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Theoretical and experimental research, presented in all the mentioned studies, have showed that the influence of low-modulus phase on the material characteristics is closely related to sizes, shapes, and the distribution of the soft inclusions within the solid matrix. As it can be concluded from numerous works [6,9,11,17,18], soft particles can not only "weaken" material but also improve its fracture resistance. This is achieved when cracks are arrested by blunting crack tips at low-Ehigh-E material interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental research, presented in all the mentioned studies, have showed that the influence of low-modulus phase on the material characteristics is closely related to sizes, shapes, and the distribution of the soft inclusions within the solid matrix. As it can be concluded from numerous works [6,9,11,17,18], soft particles can not only "weaken" material but also improve its fracture resistance. This is achieved when cracks are arrested by blunting crack tips at low-Ehigh-E material interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusions positive influence has been demonstrated by numerous investigations of heteromodulus ceramics (HMC): Si3N4-BN [5,6], TiC-C [2,7,8], B4C-BN [4,9], SiC-BN [10], TiB2-TiC-C [11], ZrB2-SiC-C [12 -15], HfB2-HfC-C [16] and glass-BN [17]. Theoretical and experimental research, presented in all the mentioned studies, have showed that the influence of low-modulus phase on the material characteristics is closely related to sizes, shapes, and the distribution of the soft inclusions within the solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Young's modulus and tensile strength of polyacrylic acid (PAA) hydrogel (water content 70 wt.%) composites were increased by 244% and 57%, respectively, when 0.5 g L −1 BNNSs was added to the PAA hydrogel 112 . This excellent reinforcement 49,67,81,92,102,105,[108][109][110]112,113,132,140,152,156,183,233,236,[245][246][247][248][249] . Fig.…”
Section: Bnns-polymer Nanocomposite Properties Mechanical Propertiesmentioning
confidence: 81%
“…9. Moreover, it was shown that the introduction of BN results in the strengthening and toughening of ceramic composites [28,82,175].…”
Section: Strengthmentioning
confidence: 99%